Impact of a potential avian flu outbreak in Ethiopia: a multimarket model analysis - Thomas, Marcelle; Diao, Xinshen; Roy, Devesh (International Food Policy Research Institute, 2009)
The potential impact of a highly pathogenic avian influenza (HPAI) outbreak in Ethiopia is assessed, specifically on the country’s poultry and associated sectors. Ethiopia has not yet experienced an HPAI outbreak but has experienced a scare. An HPAI outbreak would cause a supply and demand shock to the poultry sector. Whereas supply shocks would be related directly to the disease and be local, demand shocks would be more dispersed across regions. Results of a dynamic spatially disaggregated multimarket model indicate that, given the poultry sector’s small contribution to the Ethiopian economy, the likely overall effect of an HPAI outbreak on the economy would be small. Importantly, for the same reason that aggregate impacts are likely to be small, the livelihood impact could be large, because poor households participate significantly in poultry production.